Quality of family relationships and outcomes of dementia: a systematic review. Issue 1 (21st January 2018) - Edwards, Hannah B; Ijaz, Sharea; Whiting, Penny F; Leach, Verity; Richards, Alison; Cullum, Sarah J; Cheston, Richard IL; Savović, Jelena
Abstract : Objectives: To evaluate the association between the quality of relationship between a person with dementia and their family carer and outcomes for the person with dementia. Design: Systematic review. Eligibility criteria: Cohort studies of people with clinically diagnosed dementia and their main carers. Exposures of interest were any elements of relationship quality, for example, attachment style, expressed emotion and coping style. Our primary outcome was institutionalisation, and secondary outcomes were hospitalisation, death, quality of life and behavioural and psychiatric symptoms of dementia ('challenging behaviour'). Data sources: MEDLINE, Embase, Web of Science, PsycInfo, the Cochrane Library and Opengrey were searched from inception to May 2017. Study appraisal and synthesis methods: The Newcastle-Ottawa Scale was used to assess risk of bias. A narrative synthesis of results was performed due to differences between studies. Results: Twenty studies were included. None of the studies controlled for all prespecified confounding factors (age, gender, socioeconomic status and severity of dementia). Reporting of results was inadequate with many studies simply reporting whether associations were 'statistically significant' without providing effect size estimates or CIs. There was a suggestion of an association between relationship factors and global challenging behaviour. All studies evaluating global challenging behaviour provided statistical evidence of an association (most P values below 0.02). There was no consistent evidence for an association for any other outcome assessed. Conclusions: There is currently no strong or consistent evidence on the effects of relationship factors on institutionalisation, hospitalisation, death or quality of life for people with dementia. There was a suggestion of an association between relationship factors and challenging behaviour, although the evidence for this was weak. To improve our ability to support those with dementia and their families, further robust studies are needed. PROSPERO registration number: CRD42015020518 .